Attention Deficit Hyperactivity Disorder (ADHD) Subtypes, Co-occurring Psychiatric Symptoms and Sexual Risk Behaviors among Adolescents Receiving Substance Abuse Treatment - Regan, Timothy (Subst Use Misuse, 2019)
BACKGROUND: Adolescents entering substance abuse treatment report clustered psychiatric symptoms and sexual risk behaviors representing differential levels of impairment and risk for maladaptive health outcomes. OBJECTIVES: To examine the prevalence of Attention Deficit Hyperactivity Disorder (ADHD) subtypes among adolescents receiving outpatient substance abuse treatment; To document group differences in (a) past-year psychiatric symptom scores and (b) sexual risk behaviors by ADHD subtype and gender. METHODS: Self-report data were collected via structured interviews from 394 adolescents (280 males, M = 16.33 years, SD = 1.15 years), enrolled in an HIV/STI risk reduction intervention for adolescents receiving outpatient substance abuse treatment. ADHD diagnostic subtypes and other past-year psychiatric symptoms were assessed using the Brief Michigan Version of the Composite Internal Diagnostic Interview (UM-CIDI). Adolescents provided self-report data on sexual risk behaviors. RESULTS: Multivariate analyses of variance (MANOVAs) documented that Inattentive and Hyperactive-Impulsive ADHD subtypes were significantly associated with higher scores for all past-year psychiatric symptoms. The combined ADHD subtype was significantly associated with higher scores for all psychiatric symptoms except affective disorder. Girls reported significantly higher mean symptoms than boys for alcohol abuse and dependence, anxiety and affective disorder symptoms. Sexual risk behavior scores were not associated with ADHD status, but girls reported consistently higher scores for multiple risk behavior outcomes. Several psychiatric disorder symptoms were significant covariates of multiple sexual risk behaviors. CONCLUSION/IMPORTANCE: Brief screenings for ADHD, other psychiatric disorders and sexual risk behaviors can provide data for tailoring substance abuse services to improve adolescent health outcomes for high-risk subgroups.